Magnetic Properties of Austenitic Stainless Steel 316l and 316lvm after High Temperature Gas Nitriding Treatment - Suprihanto, Agus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2017)
Biometallic materials for implant devices not only have to good corrosion resistance but also stable nonmagnetic properties. Various method have been developed for enhanced the corrosion resistance i.e low temperature gas nitriding treatments. Unfortunatelly, low temperature gas nitriding produce weakly ferromagnetic due the presence of expanded austenitic phases. Another treatments methods which is capable for improvement the mechanical properties is high temperature gas nitriding. However, the evaluation of magnetic properties of austenitic stainless steel 316L and 316LVM not yet investigation. The evaluation of magnetic properties of austenitis stainless steel 316L and 316LVM after high temperature gas nitriding treatments have been succesfully done. The magnetic properties are evaluated by vibrating sample magnetometre (VSM) test. The magnetic properties such as magnetic remenance, magnetic saturation and magnetic permeability are improved. As treated 316L and 316LVM have more stable non-magnetic properties and they more safe and compatible for MRI test